DEVELOPMENT, EVALUATION, AND CHARACTERIZATION OF LOSARTAN POTASSIUM BUCCAL PATCHES USING JACKFRUIT POLYMER: BUCCAL PATCH - SOJI S; ARUN JL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective was to develop buccal patches of an antihypertensive drug and losartan potassium using jackfruit polymer for sustained buccal delivery. Methods: The patches were prepared by the solvent casting method. Five formulations were developed with varying concentrations of jackfruit polymer. USP type II apparatus was used to perform in-vitro release study under perfect sink condition. Buccal formulations were developed to a satisfactory level in terms of drug release, bioadhesive strength, content uniformity, moisture content, surface pH, thickness, and stability study. Results: From the results obtained F5 was found as best formulation, having appropriate folding endurance greater than 300, moisture content of 1.14±0.03 percentage (%), moisture uptake of 6.21±0.12%, swelling index (62.78%), bioadhesion strength (37.62±0.25 g), and bioadhesion time of 9 h 5 min. Fourier-transform infrared spectroscopy studies have shown no interactions between drug and polymer. All the formulations followed zero-order kinetics. Conclusion: It can be concluded that mucoadhesive buccal patches of losartan potassium using jackfruit polymer are an auspicious dosage form to prolong the release of drug and enhance its poor oral bioavailability.